Healthcare Workforce Shortages: Evidence from Communist and Postcommunist Bulgaria - Simeonova-Ganeva Ralitsa I.; Ganev Kaloyan I. (Comparative Southeast European Studies, 2025)
This study assesses healthcare workforce shortages in Bulgaria across three periods: communism (1944–1989), transition (1990–2002), and EU integration (2003 onward). Using historical data and benchmarking against European medians, the authors analyze trends among physicians, dentists, nurses, and midwives. They find that during communism, massive investment until the mid-1970s, and restricted international mobility led to significant human capital accumulation in healthcare. For the 1980s, they identify serious issues due to reduced subsidies and low remuneration. The authors point to a substantial brain drain and care drain following the labor market opening during the transition, while they argue that the reform implemented at the end of this period exacerbated nursing staff losses. For the period of EU integration, they observe positive reversals, but also emphasize that shortages persist. This, they argue, can be explained by the inability of the educational system to overcome the shortages.